2016
DOI: 10.1038/bcj.2015.110
|View full text |Cite
|
Sign up to set email alerts
|

Infectious complications in children with acute myeloid leukemia: decreased mortality in multicenter trial AML-BFM 2004

Abstract: Infections are an important cause for morbidity and mortality in pediatric acute myeloid leukemia (AML). We therefore characterized infectious complications in children treated according to the trial AML-BFM 2004. Patients with Down syndrome were excluded from the analysis. Data were gathered from the medical records in the hospital where the patients were treated. A total of 405 patients (203 girls; median age 8.4 years) experienced 1326 infections. Fever without identifiable source occurred in 56.1% of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
71
4
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(88 citation statements)
references
References 20 publications
8
71
4
5
Order By: Relevance
“…Retrospective data from study AML-BFM 93 indeed demonstrated a significantly higher VGS sepsis rate following high-dose cytarabine cycles whereas in a recent NOPHO-AML study and in the AML-BFM 2004 study, no significant difference of VGS sepsis rate was observed between lower-dose and high-dose courses [4, 9, 22]. In our study, rate of VGS sepsis was comparably high following intermediate-dose and high-dose cycles (9.3 and 7.4 %) while no VGS sepsis occurred after induction cycles with low-dose cytarabine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Retrospective data from study AML-BFM 93 indeed demonstrated a significantly higher VGS sepsis rate following high-dose cytarabine cycles whereas in a recent NOPHO-AML study and in the AML-BFM 2004 study, no significant difference of VGS sepsis rate was observed between lower-dose and high-dose courses [4, 9, 22]. In our study, rate of VGS sepsis was comparably high following intermediate-dose and high-dose cycles (9.3 and 7.4 %) while no VGS sepsis occurred after induction cycles with low-dose cytarabine.…”
Section: Discussionmentioning
confidence: 99%
“…According to data from study AML-BFM 93 and 2004, VGS was isolated in more than 20 and 30 % of cases with neutropenic bacteremia, respectively. While incidence of VGS sepsis was significantly higher after chemotherapy cycles containing high-dose cytarabine in protocol AML-BFM 93, this difference was not obvious in the 2004 study [4, 9]. Infection with VGS bears substantial risk for viridans streptococcal shock syndrome with a reported mortality rate of up to 100 % [10].…”
Section: Introductionmentioning
confidence: 99%
“…Infections were defined as clinical signs and symptoms of infection associated with the institution of antibiotics, the isolation of a pathogen, or an identifiable site of infection by physical examination or imaging study. 2,9 Infectious episodes were categorized as fever of unknown origin (FUO) or as clinically or microbiologically documented infection. Fever was defined as having a temperature above 38.5°C once or 38°C to 38.5°C twice within a 4-hour interval.…”
Section: 12mentioning
confidence: 99%
“…Fever was defined as having a temperature above 38.5°C once or 38°C to 38.5°C twice within a 4-hour interval. 2,9 Bacteremia was defined as fever with a positive blood culture for bacteria. If the bloodstream isolate was a potential skin contaminant (eg, coagulase-negative Staphylococcus), the presence of an intravascular catheter was required for the diagnosis of a bloodstream infection.…”
Section: 12mentioning
confidence: 99%
See 1 more Smart Citation